Students Difficulties In Understanding Descriptive Texts At Grade XI Of SMKS 1 Tamansiswa Pematangsiantar - Sitorus, Leony; Selviana Napitupulu (Jurnal Ilmu Sosial dan Humaniora, 2026)
Reading comprehension plays an important role in English language learning because it enables students to construct meaning, acquire knowledge, and develop language proficiency. However, many vocational school students still experience serious difficulties in understanding descriptive texts, which are an important part of the English language curriculum. Previous studies have highlighted that students often experience difficulties due to limited vocabulary, insufficient knowledge of grammar, lack of background understanding, and low motivation. However, few studies have examined this issue in the context of vocational education. Therefore, this study aims to investigate students' difficulties in understanding descriptive texts at SMK Swasta 1 Tamansiswa Pematangsiantar. This study uses a qualitative descriptive method involving observation, interviews, and document analysis to identify the types and causes of students' difficulties. The results of the study show that the main problems experienced by students are a lack of vocabulary mastery, difficulty recognizing the general structure of descriptive texts, misunderstanding of main ideas and specific information, and confusion about grammar, especially in the use of simple tenses and adjectives. In addition, low reading motivation and over-reliance on translation tools also have a negative impact on students' comprehension. This study concludes that these difficulties arise from linguistic, cognitive, and affective factors. The results of this study are expected to provide valuable insights for teachers to design more effective reading strategies and improve students' understanding of descriptive texts in English as a foreign language.